Customer Service And Communication Skills: A Scientometric Study (Journal of Namibian Studies : History Politics Culture, 2022)
The objective of this study is to analyze the contribution of scientific, academic, and business productivity disclosed on the research topic "Customer Service and Communication Skills", through the use of the Scopus database between 1978 and 2022 in all areas of knowledge because the theme is transversal to them. The methodological design used is fundamentally based on an analysis of scientific trends from scientometric tools in the development of statistics and thematic maps. The analysis allows an identification of the participation and interaction between the various authors, countries, and institutions, coupled in clusters that reveal the contexts of intellectual production. The results found indicate that of the 170 works retrieved, 84 are articles, in the average of articles cited in the study period, the year 2000 was the most relevant with 2.9, The key terms, client, service and communication were the most related to the authors Cheikh F. and Demeester P. and with the countries of Germany and France.